Strategy of politeness through Japanese respect in the anime My Next Life as a Villainess: All Routes Lead to Doom Season 1 - Demiyati, Lely; Susanti, Rita; Aziz, Hafizh Abdul (Universitas Dian Nuswantoro, 2023)
Japan is famous for its politeness in language. Politeness in Japanese is inseparable from culture. Anime is a form of global culture. Anime is also well-known as one of the reasons Japanese language learners are interested in Japanese. It is this background that makes the writer research